Introduction to secondary school teaching - Boroughs, Homer; Foster, Clifford D. ;Salyer, Rufus C. (New York : Ronald Press Company, 1964)
he authors have planned this textbook to serve as an introduction to the teaching-learning process and as a source of practical information for students who are preparing to teach in the junior or senior high school.
Chapter 1. Philosophy and educational method -- Chapter 2. The Development and nature of secondary education -- Chapter 3. Psychological considerations basic to teaching -- Chapter 4. The Secondary school student -- Chapter 5. The Teacher -- Chapter 6. Planning and the teacher -- Chapter 7. The Unit plan -- Chapter 8. The Problem and the project -- Chapter 9. Instruction through the oral use of language -- Chapter 10. Developing and guiding class discussion activity -- Chapter 11. The Use of the question in teaching -- Chapter 12. Effective use of drill and review methods -- Chapter 13. Supervised study -- Chapter 14. Classroom management, control and student discipline -- Chapter 15. The Utilization of audio-visual methods and materials.
Includes bibliographical references and index.
Keywords: EDUCATION